(untitled) (PerCursos, 2023)
The work reflects on the production of data and management of risks and disasters, in the last decade, in relation to the affectation of older people, especially those residing in Long-stay Institutions for the elderly (LSIE). For this, secondary data, legislation and literature were used. Among the results, for functioning, they must follow the legislation, normative instructions, and resolutions to guarantee protection and care for their residents. In situations of disasters, emergencies and public calamities, the situation becomes complex with the lack of data involving institutionalized elderly, and the lack of guidelines on how ILPIs and services of the elderly care network could proceed, to guarantee the protection of that segment. The article shows that the actions to protect institutionalized older people and monitor the affectation are harmed, because the topic goes unnoticed. To face the challenges of the invisibility of risk and disaster management involving LSIEs, data production, communication, technical-scientific basis in gerontology and civil protection and defense are required, as well as normative instructions to guide LSIEs and public bodies in the prevention, preparation, response and recovery involving this population segment.